Paediatric neuromyelitis optica: clinical, MRI of the brain and prognostic features. Issue 4 (4th August 2014) - Absoud, Michael; Lim, Ming J; Appleton, Richard; Jacob, Anu; Kitley, Joanna; Leite, M Isabel; Pike, Michael G; Vincent, Angela; Wassmer, Evangeline; Waters, Patrick; Woodhall, Mark; Hemingway, Cheryl; et al.
Abstract : Background: Neuromyelitis Optica (NMO) is a severe and rare inflammatory condition, where relapses are predictive of disability. Methods: We describe a national paediatric NMO cohort's clinical, MRI, outcome, and prognostic features in relation to Aquaporin-4 antibody (AQP4-Ab) status, and compared to a non NMO control cohort. Observations: Twenty NMO cases (females=90%; AQP4-Ab positive=60%; median age=10.5yrs) with median follow-up=6.1yrs were compared to a national cohort sample of known sequential AQP4-Ab negative first episode CNS acquired demyelination cases (n=29; females=55%; all AQP4-Ab negative; median age=13.6yrs). At presentation, 40% NMO cases had unilateral optic neuritis (ON); 20% bilateral ON; 15% transverse myelitis (TM); 15% simultaneous TM&ON; 10% Acute disseminated encephalomyelitis. At follow up, 55% had a clinical demyelinating episode involving the brain; 30% of cases had abnormal brain MRI at onset and 75% by follow up. NMO brain scan lesions compared to controls were large (>2 cm), acute lesions largely resolved on repeat imaging, and often showed T1 hypointense lesions. Mean time to relapse=0.76yrs (95% CI 0.43–1.1yrs) for AQP4-Ab positive vs 2.4yrs in AQP4-Ab negative cases (95% CI 1.1–3.6yrs). In AQP4-Ab positive cases, 10/12 had visual acuity<6/60 Snellen in ≥1 eye (0/8 AQP4-Ab negative), and 3 AQP4-Ab negative cases were wheelchair-dependent. Conclusions: In children, NMO is associated with early recurrence and visual impairment in AQP4-Ab positivity and physical disability in AP4-Ab negative relapsing cases. Distinct MRI changes appear more commonly and earlier compared to adult NMO. Early AQP4-Ab testing may allow prompt immunomodulatory treatment to minimise disability.